(untitled) (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
The food and beverage manufacturing sector in Indonesia plays a strategic role in the national economy and has demonstrated relatively stable growth in the post–COVID-19 period. However, revenue growth in several companies within this sector has not always been accompanied by increased profits, indicating pressure on firms’ financial performance. This study aims to examine the effect of capital structure, tax avoidance, and gender diversity on the financial performance of food and beverage manufacturing companies in Indonesia during the 2020–2024 period. Purposive sampling was employed, resulting in a sample of 85. The data were analyzed using panel data regression techniques. The findings indicate that capital structure, proxied by the Debt to Equity Ratio (DER), has a negative and significant effect on financial performance. Meanwhile, tax avoidance, proxied by the Cash Effective Tax Rate (CETR), and gender diversity, measured by the proportion of female directors, do not have a significant effect on financial performance. Simultaneously, capital structure, tax avoidance, and gender diversity significantly affect the financial performance of food and beverage manufacturing companies.